2020
DOI: 10.21831/jpv.v9i3.22017
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the stages of the educational research methodology into animation infographics for vocational students

Abstract: Visualizing something abstract into a concrete object can help students improve their mastery of concepts in learning. The purpose of this study is to visualize the stages of the educational research methodology into an animation infographic media. The method used refers to the instructional development model. The target subjects of this study were students of informatics engineering education study program who had taken courses in educational research methodology. In order to get valid, practical, and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
1
10
0
3
Order By: Relevance
“…Based on the results of study [3] that animation and descriptive infographics are very effective to use for narration. This is also supported by the results of a study [4] which proves that infographic animation is valid, practical, and effectively used in increasing mastery of concepts. The results of the study by Fandy Neta et al [5] showed that there was a significant effect on the learning algorithm subject when using the help of live shoot video media combined with animated infographics.…”
Section: Introductionsupporting
confidence: 57%
“…Based on the results of study [3] that animation and descriptive infographics are very effective to use for narration. This is also supported by the results of a study [4] which proves that infographic animation is valid, practical, and effectively used in increasing mastery of concepts. The results of the study by Fandy Neta et al [5] showed that there was a significant effect on the learning algorithm subject when using the help of live shoot video media combined with animated infographics.…”
Section: Introductionsupporting
confidence: 57%
“…Selanjutnya untuk validitas ahli media melalui penilaian instrumen angket ahli media diperoleh hasil perhitungan yaitu 1,00 yang menunjukkan bahwa produk konten interaktif ini berada pada kriteria "Sangat Valid". Selain itu, uji efektivitas dari konten pembelajaran interaktif mata pelajaran Simulasi dan Komunikasi Digital dilakukan dengan memberikan soal berupa soal pre-test dan soal post-test untuk mengetahui perbandingan nilai yang diperoleh oleh peserta didik sebelum dan sesudah diimplementasikannya penggunaan konten interaktif mata pelajaran Simulasi dan Komunikasi Digital Gain sebesar 0,91 sehingga uji efetivitas yang dilakukan berada pada kriteria "Efektif" merujuk pada tabel kategori skor Gain menurut [15].…”
Section: Gambar 1 Perancangan Struktur Konten Interaktif 3) Hasil Tahap Pengembangan (Development)unclassified
“…[1] menyatakan pendidikan sangat memerlukan pertukaran informasi agar dalam proses pembelajaran memiliki kreativitas dan inovasi. Menurut [2] menggunakan tampilan visual dalam penyampaian materi pelajaran dalam bidang pendidikan akan lebih mempercepat pemahaman dalam proses pembelajaran. Ada baiknya setiap jenjang pendidikan kini memanfaatkan kecanggihan teknologi multimedia dalam pelaksanaan proses pembelajaran, dikarenakan pada era modern dari jenjang pendidikan dasar peserta didik sebagian besar sudah melek akan teknologi.…”
Section: Pendahuluanunclassified